Airport solid waste generation and its interfaces with tourism: Hugo Cantergiani Airport’s case, Caxias do Sul-RS, Brazil - Jaciel Gustavo Kunz; Suzana Maria De Conto; Morgana Klipp Demori (Revista Brasileira de Pesquisa em Turismo, 2015)
The tourism phenomenon cannot be separated of transport systems and it needs to be examined in the light of the environmental dimension, in particular the air mode. The aim of this research was to investigate the situation of solid waste generation at Hugo Cantergiani Airport, located in Caxias do Sul-RS. The research, which applied a descriptive and exploratory approach, involved document survey, direct observation and solid waste characterization. The period of the sample was of 18 and a half days, spread over three weeks/months in 2012. The operational movimentation at the airport during the conduct of the research was of 15,543 passengers. At the time of the sample 878.76 kg of waste were weighed of which 606.83 kg were segregated and characterized. In relation to this amount around 70% were derived from services undertaken at the airport site and around 30% came from the aircraft itself. The results revealed that there was a production by passenger at the aircraft of 30g/passenger/trip and at the airport site a per capita production of 40g/person/day. The most representative components were as follows: biological contaminant (29.54%), putrescible organic matter (27.16%), plastic (19.15%) and paper and paperboard (14.04%). These types of studies contribute to fill gaps in knowledge related to the gravimetric composition of solid waste in the context of airports, to assess the environmental impacts caused by the generation of such wastes and to provide guidelines for the management plan of solid waste at airports, tourism supporting infrastructures.